Augmented Reality (AR) for Soil Health Assessment: A Visual Guide for Farmers in Resource-Limited Agricultural Zones - Dwi Mei Laraswati; Chiska Nova Harsela; Indi Millatul Maula; Pegi Sugiartini; Komarudin (Politeknik Siber Cerdika Internasional, 2025)
The rapid advancement of digital technologies presents a significant opportunity for improving agricultural practices, particularly in resource-limited zones. Augmented Reality (AR) offers farmers an innovative real-time soil health assessment solution, enabling them to make informed decisions about irrigation, fertilization, and crop management. This study aims to evaluate the effectiveness of an AR-based soil health assessment tool tailored for smallholder farmers. A qualitative research approach was employed, using in-depth interviews and field observations with 20 farmers from rural agricultural areas. The tool provided real-time data on critical soil parameters, including moisture, nutrient levels, and pH balance. Results indicate that the AR tool significantly improved farmers’ ability to manage soil health, leading to more efficient water usage and optimized fertilizer application. However, challenges such as internet connectivity and digital literacy barriers were observed. Overall, the tool was found to be a valuable asset in promoting sustainable farming practices in low-resource areas. Future research should explore offline functionalities and broader applications of AR technology in agriculture.